(untitled) (Research, Society and Development, 2020)
The aim of this study was to compare the cost of the paleolithic (PD) diet with that of the traditional diet supported by guidelines (DTG) in obese patients treated by the Brazilian public health system. It is a randomized clinical trial with obese patients who were divided into two groups according to the dietary prescription: DP and DTG, involving, respectively, 82 and 73 patients. They were followed up for 30 and 60 days, with two monthly 24h (R24h) reminders. A cost-effectiveness analysis of the DP and DTG diets was performed. The daily cost of each R24h was calculated with the aid of the PROCONOMIZE tool, a free application available on the IOS platform. As a measure of efficiency or outcome, the patient’s weight loss variable was used, and the average cost ratio was calculated by varying the patients’ weight. The cost-effectiveness calculation was carried out taking into account the cost ratio, considering the standard deviation, for efficiency. There was no difference between groups in terms of demographic, socioeconomic, nutritional status and usual expenditure on daily food before starting treatment. Regarding the average cost, the DP proved to be more economical when compared to the DTG. In addition, PD is more efficient, as it has a lower cost-effectiveness ratio, both at 30 days and 60 days, in addition to greater weight loss, when compared to DTG. PD is a viable option for treating obesity, with a similar cost to DTG.